Association between diabetes status and breast cancer in US adults: findings from the US National Health and Nutrition Examination Survey - Sun, Xingyu; Zhang, Qiangsong; Kadier, Kaisaierjiang; Hu, Pengcheng; Liu, Xiaozhu; Liu, Jialing; Yan, Yulu; Sun, Chenyu; Yau, Vicky; Lowe, Scott; Meng, Muzi; Liu, Ziru; et al. (Frontiers in Endocrinology, 2023)
Objectives The aim of this study was to investigate the association between diabetes status and the risk of breast cancer among adult Americans, exploring the impact of BMI, age, and race on this relationship. Methods A cross-sectional analysis of 8,249 individuals from the National Health and Nutrition Examination Survey (NHANES) was conducted. Diabetes was categorized as type 2 diabetes and prediabetes, with both conditions diagnosed according to the ADA 2014 guidelines. The association between diabetes status and breast cancer risk was explored using multiple logistic regression analysis. Results Patients with diabetes had higher odds of breast cancer (OR: 1.51; 95% CI 1.00 to 2.28), Using the two-piecewise linear regression model, it was observed that there is a threshold effect in the risk of breast cancer occurrence at the age of 52 years. Specifically, the risk of breast cancer is relatively low before the age of 52 but increases significantly after this age. Conclusions This study identified a significant association between diabetes status and breast cancer risk among adult Americans. We also found a threshold effect in breast cancer occurrence at the age of 52. Age was significantly associated with breast cancer risk in both Non-Hispanic White and Non-Hispanic Black individuals. These findings underscore the importance of diabetes management, maintaining a healthy BMI, and age-related risk considerations in reducing breast cancer risk.